Orientasi Filosofis Penyelenggaraan Pendidikan Anak Usia Dini - Rita Sulastini (INSANIA : Jurnal Pemikiran Alternatif Kependidikan, 2015)
Abstract: Education since the early childhood is the greatest content and become an investment for education in the future. Early Childhood Education (ECD) become one level of education which was instrumental in introducing systematic directionally life of a child with a variety of patterns and formats. Therefore philosophically, Early Childhood Education is not talking about ‘learning’ something or get to know new things. Early Childhood Education actually promote the formation of a child’s orientation on any matter that requires processes and interaction to things that can enrich naturally he thought nature. Keywords: care concept, environmental management.